Biomechanical consequences of anterior root detachment of the lateral meniscus and its reinsertion - Espejo-Reina, Alejandro; Prado-Novoa, María; Espejo-Baena, Alejandro; Peña Trabalón, Alejandro; Pérez-Blanca, Ana (Springer Nature, 2022)
Treatment of posterior meniscal roots tears evolved after biomechanical evidence of increased pressures on the tibiofemoral cartilage produced by this lesion and the subsequent accelerated development of arthritis or osteonecrosis observed clinically. However, little is known about the consequences of the detachment of the anterior roots. This in-vitro study analyzes the biomechanical changes in the tibiofemoral joint caused by avulsion of the anterior root of the lateral meniscus. The effectiveness of surgical root re-insertion to restore the pre-injured conditions is also evaluated. Using cadaveric knees at flexion angles from 0° to 90°, results show that the lesion significantly reduces the contact area and raises the pressure on the tibiofemoral cartilage of the injured compartment at all angles. Said modifications become larger at low flexion angles, which are the most frequent positions adopted by the knee in daily and sports activities, where they result similar to total meniscectomy. In-situ repair partially restores the contact biomechanics. Consequently, careful attention should be paid to proper diagnosis and treatment of detached anterior roots since the observed altered knee contact might induce similar degenerative problems in the cartilage as with completely detached posterior roots.
Keywords: Biomecánica; Meniscal suture; Reinsertion; Experimental; Biomechanics; Meniscal root detachment